STUDI KORELASI PENERAPAN E-ASSESSMENT TERHADAP PERKEMBANGAN KEMAMPUAN REGULASI DIRI SISWA SEKOLAH MENENGAH ATAS - Giati Anisah; Aufa, Ari Abi (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2022)
This research is quantitative research with the type of correlation research. This study analyzed the correlation between the implementation of e-assessment and the development of self-regulation abilities. The populations are senior high school students in Tuban and Bojonegoro regencies, either SMA, MA, or SMK. Sampling was taken by cluster random sampling technique. Hypothesis testing was carried out using a simple regression technique through the SPSS for Windows application. The data were tested for normality and linearity before testing the hypothesis. Based on the results of the analysis, it was concluded that there was a significant positive relationship between the implementation of e-assessment and the development of students' self-regulation abilities. This significant relationship can be seen from the correlation coefficient of 0.685 with a value of p = 0.000 (p>0.05).